2019
DOI: 10.1002/stc.2370
|View full text |Cite
|
Sign up to set email alerts
|

A bolt preload monitoring method based on the refocusing capability of virtual time reversal

Abstract: Bolted joints are widely used in aerospace and civil structures. Nevertheless, bolts may easily lose preload because of inappropriate initial preloads or time-varying servicing loads. Hence, bolt loosening monitoring is important for ensuring the safety and reliability of the bolt-jointed structures. In this paper, a guided wave method based on virtual time reversal (VTR) and tightness index representing refocusing capability is developed for bolt preload monitoring and to mitigate the requirement of baseline.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Wang et al 10 developed a new entropy-based damage index using the multi-scale permutation entropy algorithm, which eliminates the saturation phenomenon of the current damage index and enhances the performance of bolt early looseness monitoring. Du et al 11 proposed a guided wave method based on virtual time reversal and tightness index for bolt preload monitoring. The experimental results showed that the tightness index increased almost linearly as the bolt preload decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 10 developed a new entropy-based damage index using the multi-scale permutation entropy algorithm, which eliminates the saturation phenomenon of the current damage index and enhances the performance of bolt early looseness monitoring. Du et al 11 proposed a guided wave method based on virtual time reversal and tightness index for bolt preload monitoring. The experimental results showed that the tightness index increased almost linearly as the bolt preload decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Mainstream contact methods primarily utilize piezoelectric transducers (PZT) attached to the structures of interest for damage detection. By attaching two PZT patches to each side of bolt joint, 2–5 bolted preload could be discerned by quantifying energy intensity of the stress wave propagating through joint interfaces 6 . Further, a PZT‐integrated smart washer was designed to allow long‐term detection of axial stress changes of fastened bolts 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, bolted connections are prone to losing sufficient preload, which may result in disasters. Several methods have been proposed to detect bolt looseness, such as acoustic emission method, 3 vision-based methods, 4,5 active sensing method, [6][7][8][9] electromechanical impedance (EMI) method, [10][11][12] vibro-acoustic modulation method, 13,14 vibration-based method, 15 fiber-optic-based method, 16,17 and percussion-based method. [18][19][20][21][22] Though the above approaches have demonstrated promising performance, they all focus on the detection of single-bolt looseness, which is unsuitable for flanges.…”
Section: Introductionmentioning
confidence: 99%